Nanotechnology 2010
DOI: 10.1002/9783527628155.nanotech040
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic and Hybrid Spintronics

Abstract: “Spintronics” is the science and technology of using the spin degree of freedom of a charge carrier, either singly or in conjunction with the charge, to store, process and/or communicate information. Both, classical and quantum mechanical information can be encoded by spin. In this chapter, “hybrid” and “monolithic” spintronics are discussed; the distinction between the two is that, in the former case, spin is not used directly to store or process information; rather, that role is still delegated to charge. Bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…By increasing V EP , the Ti foil surface became slightly rougher: Rq = 3.4, 4.7, and 3.1 nm measured for samples 15, 18, and 20 V, respectively. Additionally, the Ti surface after EP revealed a periodic dimple-pattern structure whenever V EP was no smaller than 10 V. This shallow ripple-like structure is an EP characteristic of metals [34,42] and can be used as a pre-pattern prior to anodization to obtain highly ordered oxide nanostructures, as profusely shown in the case of Al [28,[34][35][36][37]41]. In fact, studies in Al foils demonstrated that, by combining adequate EP voltage and time, dimplepatterns from striped to hexagonal arrangements can be obtained [28,[34][35][36][37]41].…”
Section: Afm Imaging Analyses: Surface Topography and Roughness Chara...mentioning
confidence: 79%
See 4 more Smart Citations
“…By increasing V EP , the Ti foil surface became slightly rougher: Rq = 3.4, 4.7, and 3.1 nm measured for samples 15, 18, and 20 V, respectively. Additionally, the Ti surface after EP revealed a periodic dimple-pattern structure whenever V EP was no smaller than 10 V. This shallow ripple-like structure is an EP characteristic of metals [34,42] and can be used as a pre-pattern prior to anodization to obtain highly ordered oxide nanostructures, as profusely shown in the case of Al [28,[34][35][36][37]41]. In fact, studies in Al foils demonstrated that, by combining adequate EP voltage and time, dimplepatterns from striped to hexagonal arrangements can be obtained [28,[34][35][36][37]41].…”
Section: Afm Imaging Analyses: Surface Topography and Roughness Chara...mentioning
confidence: 79%
“…Additionally, the Ti surface after EP revealed a periodic dimple-pattern structure whenever V EP was no smaller than 10 V. This shallow ripple-like structure is an EP characteristic of metals [34,42] and can be used as a pre-pattern prior to anodization to obtain highly ordered oxide nanostructures, as profusely shown in the case of Al [28,[34][35][36][37]41]. In fact, studies in Al foils demonstrated that, by combining adequate EP voltage and time, dimplepatterns from striped to hexagonal arrangements can be obtained [28,[34][35][36][37]41]. However, EP of Ti is usually performed in sulphuric acid-based electrolytes that lead to smooth and plane surfaces [31].…”
Section: Afm Imaging Analyses: Surface Topography and Roughness Chara...mentioning
confidence: 79%
See 3 more Smart Citations